Ease and Risk Perception: Interest in Using Sharia Digital Payments, and the Users' Attitude Consequences - Latief, Fitriani; Suriyanti, Suriyanti; Amin, Asbi; Mahmud, Amir; Firman, Ahmad; Dirwan, Dirwan (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
This study explores the unique role of Sharia compliance in shaping user behavior toward digital payment systems, focusing on the Islamic digital-payment platform. It aims to examine how perceived convenience, and perceived risk influence attitudes and interests in adopting Sharia-compliant digital payments. Using a quantitative approach, the research targets the users of LinkAja Sharia, Indonesia, employing purposive judgment sampling resulting in 150 response rates. Data were analyzed through Structural Equation Modeling Partial Least Square (PLS- SEM). The findings indicate that perceived convenience and perceived risk significantly and positively affect both attitudes and interest. Moreover, attitudes mediate the relationship between these perceptions and interest. The study underscores how aligning financial technology with Islamic principles adds trust and appeal, offering valuable insights for developers aiming to integrate ethical and religious values into fintech innovations for Muslim markets, and global endeavors.